Immune escaping of the novel genotypes of human respiratory syncytial virus based on gene sequence variation - Zhou, Xiaohe; Jiang, Mingli; Wang, Fengjie; Qian, Yuan; Song, Qinwei; Sun, Yu; Zhu, Runan; Wang, Fang; Qu, Dong; Cao, Ling; Ma, Lijuan; Xu, Yanpeng; et al. (Frontiers in Immunology, 2023)
Purpose: Immune escaping from host herd immunity has been related to changes in viral genomic sequences. The study aimed to understand the diverse immune responses to different subtypes or genotypes of human respiratory syncytial virus (RSV) in pediatric patients. Methods: The genomic sequences of different subtypes or RSV genotypes, isolated from Beijing patients, were sequenced and systematically analyzed. Specifically, the antiviral effects of palivizumab and the cross-reactivity of human sera from RSV-positive patients to different subtypes or genotypes of RSV were determined. Then, the level of 38 cytokines and chemokines in respiratory and serum samples from RSV-positive patients was evaluated. Results: The highest nucleotide and amino acid variations and the secondary and tertiary structure diversities among different subtypes or genotypes of RSV were found in G, especially for genotype ON1 with a 72bp-insertion compared to NA1 in subtype A, while more mutations of F protein were found in the NH-2 terminal, including the antigenic site II, the target of palivizumab, containing one change N276S. Palivizumab inhibited subtype A with higher efficiency than subtype B and had stronger inhibitory effects on the reference strains than on isolated strains. However, RSV-positive sera had stronger inhibitory effects on the strains in the same subtypes or genotypes of RSV. The level of IFN-α2, IL-1α, and IL-1β in respiratory specimens from patients with NA1 was lower than those with ON1, while there were higher TNFα, IFNγ, IL-1α, and IL-1β in the first serum samples from patients with ON1 compared to those with BA9 of subtype B. Conclusions: Diverse host immune responses were correlated with differential subtypes and genotypes of RSV in pediatric patients, demonstrating the impact of viral genetics on host immunity.